Arabidopsis WRKY6 Transcription Factor Acts as a Positive Regulator of Abscisic Acid Signaling during Seed Germination and Early Seedling Development. - Yun Huang; Cui-Zhu Feng; Qing Ye; Wei-Hua Wu; Yi-Fang Chen (PLoS Genetics, 2016)
The phytohormone abscisic acid (ABA) plays important roles during seed germination and early seedling development. Here, we characterized the function of the Arabidopsis WRKY6 transcription factor in ABA signaling. The transcript of WRKY6 was repressed during seed germination and early seedling development, and induced by exogenous ABA. The wrky6-1 and wrky6-2 mutants were ABA insensitive, whereas WRKY6-overexpressing lines showed ABA-hypersensitive phenotypes during seed germination and early seedling development. The expression of RAV1 was suppressed in the WRKY6-overexpressing lines and elevated in the wrky6 mutants, and the expression of ABI3, ABI4, and ABI5, which was directly down-regulated by RAV1, was enhanced in the WRKY6-overexpressing lines and repressed in the wrky6 mutants. Electrophoretic mobility shift and chromatin immunoprecipitation assays showed that WRKY6 could bind to the RAV1 promoter in vitro and in vivo. Overexpression of RAV1 in WRKY6-overexpressing lines abolished their ABA-hypersensitive phenotypes, and the rav1 wrky6-2 double mutant showed an ABA-hypersensitive phenotype, similar to rav1 mutant. Together, the results demonstrated that the Arabidopsis WRKY6 transcription factor played important roles in ABA signaling by directly down-regulating RAV1 expression.